Acceptance and Commitment Therapy for Co‐Occurring Posttraumatic Stress Disorder and Alcohol Use Disorders in Veterans: Pilot Treatment Outcomes. Issue 5 (19th October 2018) - Meyer, Eric C.; Walser, Robyn; Hermann, Barbara; La Bash, Heidi; DeBeer, Bryann B.; Morissette, Sandra B.; Kimbrel, Nathan A.; Kwok, Oi‐Man; Batten, Sonja V.; Schnurr, Paula P.
Abstract: Posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD) frequently co‐occur and are associated with worse outcomes together than either disorder alone. A lack of consensus regarding recommendations for treating PTSD–AUD exists, and treatment dropout is a persistent problem. Acceptance and Commitment Therapy (ACT), a transdiagnostic, mindfulness‐ and acceptance‐based form of behavior therapy, has potential as a treatment option for PTSD–AUD. In this uncontrolled pilot study, we examined ACT for PTSD–AUD in 43 veterans; 29 (67%) completed the outpatient individual therapy protocol (i.e., ≥ 10 of 12 sessions). Clinician‐assessed and self‐reported PTSD symptoms were reduced at posttreatment, d s = 0.79 and 0.96, respectively. Self‐reported symptoms of PTSD remained lower at 3‐month follow‐up, d = 0.88. There were reductions on all alcohol‐related outcomes (clinician‐assessed and self‐reported symptoms, total drinks, and heavy drinking days) at posttreatment and 3‐month follow‐up, dmean = 0.91 ( d range: 0.65–1.30). Quality of life increased at posttreatment and follow‐up, d s = 0.55–0.56. Functional disability improved marginally at posttreatment, d = 0.35; this effect became significant by follow‐up, d = 0.52. Fewer depressive symptoms were reported at posttreatment, d = 0.50, and follow‐up, d = 0.44. Individuals experiencing suicidal ideation reported significant reductions by follow‐up. Consistent with the ACT theoretical model, these improvements were associated with more between‐session mindfulness practice and reductions in experiential avoidance and psychological inflexibility. Recommendations for adapting ACT to address PTSD–AUD include assigning frequent between‐session mindfulness practice and initiating values clarification work and values‐based behavior assignments early in treatment. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Terapia de Aceptación y Compromiso para la co‐ocurrencia de Trastornos de Estrés Postraumático y Consumo de Alcohol en Veteranos: Resultados de un Tratamiento Piloto ACT PARA TEPT Y ALCOHOL El trastorno de estrés postraumático (TEPT) y el trastorno por consumo de alcohol (AUD, por sus siglas en inglés) ocurren frecuentemente de forma simultánea y están asociados con resultados peores cuando se encuentran juntos que cuando se encuentra cada uno por separado. Existe una falta de consenso con respecto a las recomendaciones para el tratamiento de TEPT‐AUD, y el abandono del tratamiento es un problema persistente. La terapia de aceptación y compromiso (ACT, por sus siglas en inglés), es una forma de terapia conductual basada en el transdiagnóstico, el mindfulness y la aceptación, tiene potencial como una opción de tratamiento para TEPT‐AUD. En este estudio piloto no controlado, examinamos la ACT para TEPT‐AUD en 43 veteranos; 29 (67%) completaron el protocolo de terapia individual ambulatoria (es decir, ≥ 10 de 12 sesiones). Los síntomas de TEPT autorreportados y evaluados por el médico se redujeron en el postratamiento, ds = 0.79 y 0.96, respectivamente. Los síntomas autorreportados de TEPT se mantuvieron más bajos a los 3 meses de seguimiento, d = 0.88. Hubo reducciones en todos los resultados relacionados con el alcohol (síntomas evaluados por el médico y autoinformados, total de bebidas alcohólicas, días de consumo excesivo de alcohol) en el postratamiento y el seguimiento a los 3 meses, d promedio = 0.91 (rango d : 0.65‐1.30). La calidad de vida aumentó en el postratamiento y el seguimiento, ds = 0.55‐0.56. La discapacidad funcional mejoró marginalmente en el postratamiento, d = 0.35; este efecto se volvió significativo en el seguimiento, d = 0.52. Se informaron menos síntomas depresivos en el postratamiento, d = 0.50 y seguimiento, d = 0.44. Los individuos que experimentaron ideación suicida informaron reducciones significativas en el seguimiento. De acuerdo con el modelo teórico de ACT, estas mejoras se asociaron con más prácticas de mindfulness entre sesiones y las reducciones en la evitación experiencial y la inflexibilidad psicológica. Las recomendaciones para adaptar ACT para abordar el TEPT‐AUD incluyen la asignación frecuente de práctica de mindfulness entre sesiones e iniciar el trabajo de aclaración de valores y tareas conductuales basadas en valores al principio del tratamiento. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Acceptance and Commitment Therapy for Co‐Occurring PTSD and Alcohol Use Disorders in Veterans: Pilot Treatment Outcomes Traditional Chinese 標題: 對同時患PTSD和酒精使用失常的退役軍人採用接受與承諾療法:試驗性治療結果 撮要: 創傷後壓力症(PTSD)和酒精使用失常(AUD)經常同時出現, 構成的後果比患單一疾病更為惡劣。對於PTSD–AUD治療, 我們一直欠缺共識, 而患者中途放棄治療的問題持續。接受與承諾療法(ACT)是跨診斷、以正念和接受為本的行為療法, 有可能是用以治療PTSD–AUD的一個選項。在這非對照的試驗研究, 我們檢視43名退役軍人接受ACT以治療PTSD–AUD的情況。當中29位(67%)完成了門診獨立治療的口語記錄(即 ≥ 10節段, 共12 節段)。臨床診斷所得及自評的PTSD症狀在完成治療後都有所減少(分別為 ds = 0.79 和 0.96)。3個月後, 自評的PTSD症狀仍有減輕(d = 0.88)。在完成治療時和3個月後, 所有酒精相關的狀況 (臨床診斷及自評的症狀、酒精使用總量、大量飲酒的日數) 都有減輕, d 平均值 = 0.91 (d 值域: 0.65–1.30)。生活質素在完成治療時和跟進期都有改善(ds = 0.55– 0.56)。功能性損傷在完成治療時有少量改善(d = 0.35), 而在跟進期的改善變得顯著(d = 0.52)。樣本的抑鬱症狀在完成治療時和跟進期都有減少(d = 0.50, 跟進期 d = 0.44)。有自殺意念的樣本, 意念在跟進期顯著減輕。與ACT的理論模型相符, 以上改善跟在節段間有更多正念練習, 以及經驗迴避及心理缺乏彈性的情況減少有關。我們對於以ACT治療PTSD–AUD的建議, 包括吩咐患者在節段間經常進行正念練習, 並在療程初期開始與患者進行價值澄清及價值為本的行為練習。 Simplified Chinese 标题: 对同时患PTSD和酒精使用失常的退役军人采用接受与承诺疗法:试验性治疗结果 撮要: 创伤后压力症(PTSD)和酒精使用失常(AUD)经常同时出现, 构成的后果比患单一疾病更为恶劣。对于PTSD–AUD治疗, 我们一直欠缺共识, 而患者中途放弃治疗的问题持续。接受与承诺疗法(ACT)是跨诊断、以正念和接受为本的行为疗法, 有可能是用以治疗PTSD–AUD的一个选项。在这非对照的试验研究, 我们检视43名退役军人接受ACT以治疗PTSD–AUD的情况。当中29位(67%)完成了门诊独立治疗的口语记录(即 ≥ 10节段, 共12 节段)。临床诊断所得及自评的PTSD症状在完成治疗后都有所减少(分别为 ds = 0.79 和 0.96)。3个月后, 自评的PTSD症状仍有减轻(d = 0.88)。在完成治疗时和3个月后, 所有酒精相关的状况 (临床诊断及自评的症状、酒精使用总量、大量饮酒的日数) 都有减轻, d 平均值 = 0.91 (d 值域: 0.65–1.30)。生活质素在完成治疗时和跟进期都有改善(ds = 0.55– 0.56)。功能性损伤在完成治疗时有少量改善(d = 0.35), 而在跟进期的改善变得显著(d = 0.52)。样本的抑郁症状在完成治疗时和跟进期都有减少(d = 0.50, 跟进期 d = 0.44)。有自杀意念的样本, 意念在跟进期显著减轻。与ACT的理论模型相符, 以上改善跟在节段间有更多正念练习, 以及经验回避及心理缺乏弹性的情况减少有关。我们对于以ACT治疗PTSD–AUD的建议, 包括吩咐患者在节段间经常进行正念练习, 并在疗程初期开始与患者进行价值澄清及价值为本的行为练习。